Homonymous Hemianopia dan Stroke: Aspek Visual dari Penyakit Serebrovaskular - Aulia Khairunnisa (Utan Kayu Publishing, 2021)
Visual impairment due to stroke impacts quality of life and causes loss of vision pathways and depression. Vascular occlusion in afferent or efferent visual pathways can cause a myriad of effects. Homonymous hemianopia is a visual field list that, if there is a lesion in one area, can cause visual disturbances. Vascular causes are the most common cause of lesion occlusion in the retro chiasmal visual pathway. Clinical manifestations can include blindness of one eye, bitemporal hemianopia, binasal hemianopia, hemianopia homonym dextra / left. In the history, the patient often complains of crashing while walking, tripping easily, reduced visual fields, especially difficulty while driving. Visual field tests in the form of confrontation, campimeter or perimeter tests, sometimes a head CT-scan radiological examination is needed to help see any small infarction/mass. Stroke is the most common cause. Homonymous hemianopia, cerebrovascular involvement can be identified by knowing the anatomy of the optic tract, including monocular visual loss due to prechiasmal ischaemia, bitemporal hemianopia due to chiasmal ischaemia, Eefferent visual dysfunction due to lesions outside the afferent visual pathways. Gangguan penglihatan akibat stroke berdampak pada kualitas kehidupan dan menyebabkan hilangnya jaras penglihatan dan depresi. Oklusi vaskular pada jalur visual aferen atau eferen dapat menyebabkan banyak sekali efek. Homonymus hemianopia merupakan dafek lapang pandang yang apabila terdapat lesi disuatu bagian dapat menyebabkan gangguan penglihatan. Penyebab vaskular menjadi penyebab tersering oklusi lesi pada jalur visual retrochiasmal. Manifestasi klinis dapat berupa kebutaan satu mata, hemianopia bitemporal, hemianopia binasal, hemianopia homonim dextra/sinistra.Pada anamnesis yan sering dikeluhkan pasien sering menabrak saat berjalan, mudah tersandung, lapang pandang berkurang, terutama kesulitan saat berkendara. Uji lapang pandang berupa uji konfrontasi, kampimeter atau perimeter, terkadang dibutuhkan pemeriksaan radiologi CT-Scan kepala untuk membantu melihat adanya infark/massa yang kecil. Stroke merupakan penyebab tersering Homonymus hemianopia, keterlibatan serebrovaskular dapat diketahui lokasinya dengan mengetahui anatomi dari traktus optikus, diantaranya monocular visual loss due to prechiasmal ischaemia, Bitemporal hemianopia due to chiasmal ischaemia, Efferent visual dysfunction due to lesions outside the afferent visual pathways.